1987
DOI: 10.1530/acta.0.1150521
|View full text |Cite
|
Sign up to set email alerts
|

An implant of a gonadotropin releasing hormone agonist (buserelin) which suppresses ovarian function in the macaque for 3–5 months

Abstract: Four adult female stumptailed macaque monkeys with regular menstrual cycles and one with irregular cycles and dysfunctional uterine bleeding were treated with a single implant containing 2.6 mg of the GnRH agonist buserelin in a matrix of polylactide/ glycolide copolymer (75:25). The implant was used as a cylindrical rod of 0.8 \m=x\ 0.12 cm and implanted sc in the abdominal wall. The insertion of the implant was followed by a modest rise in serum concentrations of LH and FSH lasting 3\ p=n-\ 4 days before fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The remaining 24 animals were infused continuously for 6 weeks with the GnRH agonist D-Ser(Bul)6GnRH(l-9)-nonapeptide-ethylamide (buserelin; kindly supplied by Dr J. Sandow, Hoechst A. G, Frankfurt, F.R.G). The buserelin was incorporated into 0-8 012 cm rod implants made of a slowly biodegradable polylactide/ glycolide copolymer (molar ratio 75:25 polylactide to glycolide) previously described by Fraser, Sandow & Seidel (1987). Each implant contained 3-3 mg buser¬ elin.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 24 animals were infused continuously for 6 weeks with the GnRH agonist D-Ser(Bul)6GnRH(l-9)-nonapeptide-ethylamide (buserelin; kindly supplied by Dr J. Sandow, Hoechst A. G, Frankfurt, F.R.G). The buserelin was incorporated into 0-8 012 cm rod implants made of a slowly biodegradable polylactide/ glycolide copolymer (molar ratio 75:25 polylactide to glycolide) previously described by Fraser, Sandow & Seidel (1987). Each implant contained 3-3 mg buser¬ elin.…”
Section: Methodsmentioning
confidence: 99%
“…The implants were made of slowly biodegradable polylactic/glycolide (molar ratio 75: 25) sterilized by gamma radiation. The LHRH agonist implant was administered during the early follicular phase of the cycle as described previously (Fraser et a!, 1987). The macaques were sedated using ketamine hydrochloride (Vetalar: Parke, Davis and Co., Pontypool, Gwent, UK) and the implant was injected s.c. in the lateral region of the abdominal wall using a sterile applicator.…”
Section: Methodsmentioning
confidence: 99%
“…Inter-and intra-assay coefficients of variance were 15 and 11 % respectively. To determine the day of the preovulatory LH surge, serum LH was measured by radioimmunoassay (Fraser et a!, 1987). Progesterone was determined as described previously (Fraser et al, 1986) using a rabbit antibody R31.…”
Section: Methodsmentioning
confidence: 99%
“…To date, these slow release formulations have been based upon incorporation of GnRH agonist in a matrix of polylactide/glycolide copolymers (PLG) and administered as a small rod or as microcapsules (6,(11)(12)(13)(14)(15). The matrix material must sat¬ isfy a number of criteria; be non-irritant, non-toxic and non-carcinogenic and allow release of the pep¬ tide at a controlled optimal rate.…”
mentioning
confidence: 99%
“…While the release profile can be followed in serum, we have found that urinary levels can be detected over a longer period. The effects of the implants on endocrine changes during the men¬ strual cycle and the reversibility from implant sup¬ pression were assessed in the stumptailed ma¬ caque, a species we have used extensively for investigations into the effects of GnRH analogues (5)(6)(7)(8)(9)(10)(11)16,17).…”
mentioning
confidence: 99%